The Chinese wild grapevine (Vitis pseudoreticulata) E3 ubiquitin ligase Erysiphe necator‐induced RING finger protein 1 (EIRP1) activates plant defense responses by inducing proteolysis of the VpWRKY11 transcription factor. Issue 3 (31st July 2013) - Yu, Yihe; Xu, Weirong; Wang, Jie; Wang, Lei; Yao, Wenkong; Yang, Yazhou; Xu, Yan; Ma, Fuli; Du, Yangjian; Wang, Yuejin
Summary: Ubiquitin‐mediated regulation responds rapidly to specific stimuli; this rapidity is particularly important for defense responses to pathogen attack. Here, we investigated the role of the E3 ubiquitin ligase Erysiphe necator ‐induced RING finger protein 1 (EIRP1) in the defense response of Chinese wild grapevine Vitis pseudoreticulata . The regulatory function of E3 ubiquitin ligase EIRP1 was investigated using molecular, genetic and biochemical approaches. EIRP1 encodes a C3HC4‐type Really Interesting New Gene (RING) finger protein that harbors E3 ligase activity. This activity requires the conserved RING domain, and VpWRKY11 also interacts with EIRP1 through the RING domain. VpWRKY11 localizes to the nucleus and activates W‐box‐dependent transcription in planta . EIRP1 targeted VpWRKY11 in vivo, resulting in VpWRKY11 degradation. The expression of EIRP1 and VpWRKY11 responds rapidly to powdery mildew in Vitis pseudoreticulata grapevine; also, overexpression of EIRP1 in Arabidopsis confers enhanced resistance to the pathogens Golovinomyces cichoracearum and Pseudomonas syringae pv tomato DC3000. Our data suggest that the EIRP1 E3 ligase positively regulates plant disease resistance by mediating proteolysis of the negative regulator VpWRKY11 via degradation by the 26S proteasome.